2007
DOI: 10.1515/jbnst-2007-0303
|View full text |Cite
|
Sign up to set email alerts
|

Regional Spillovers and Spatial Heterogeneity in Matching Workers and Employers in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Burgess and Profit (2001) proved that high unemployment levels in neighbouring areas increased the number of filled vacancies in a given (local) area, but decreased the local outflow from unemployment; high vacancy levels in neighbouring areas raised the local outflow from unemployment and the local outflow of filled vacancies. Similar findings were obtained by Ilmakunnas and Pesola (2003) and Kosfeld (2007). Ilmakunnas and Pesola (2003) showed that unemployment figures in the surrounding areas exerted a negative effect on local labour markets, and that vacancies exerted a positive effect.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Burgess and Profit (2001) proved that high unemployment levels in neighbouring areas increased the number of filled vacancies in a given (local) area, but decreased the local outflow from unemployment; high vacancy levels in neighbouring areas raised the local outflow from unemployment and the local outflow of filled vacancies. Similar findings were obtained by Ilmakunnas and Pesola (2003) and Kosfeld (2007). Ilmakunnas and Pesola (2003) showed that unemployment figures in the surrounding areas exerted a negative effect on local labour markets, and that vacancies exerted a positive effect.…”
Section: Introductionsupporting
confidence: 81%
“…Ilmakunnas and Pesola (2003) showed that unemployment figures in the surrounding areas exerted a negative effect on local labour markets, and that vacancies exerted a positive effect. Kosfeld (2007) found that the strength of these effects was not stable across space. Hynninen (2005) proved that the congestion effect arose among job seekers in local labour markets, and was strengthened by spatial spillovers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kosfeld (2006), for example, finds differences in labor mobility between East and West Germany, and Molloy et al (2011) find differences in labor mobility across US regions. Furthermore, differences in the liquidity of the housing market and, thereby, in the transmission of price information and search costs could result in different amounts of information asymmetries across regions.…”
Section: Theoretical Aspects and Empirical Evidencementioning
confidence: 99%
“…Some of the more specific works on labor market matching center on Germany and consider various levels of spatial aggregation. Among the most influential research is the paper by Kosfeld ( 2007 ). The author focused on German regions and proved that matching function coefficients estimations are not stable over space.…”
Section: Introductionmentioning
confidence: 99%